Does perturbation-based balance training prevent falls among individuals with chronic stroke? A randomised controlled trial. Issue 8 (17th August 2018) - Mansfield, Avril; Aqui, Anthony; Danells, Cynthia J; Knorr, Svetlana; Centen, Andrew; DePaul, Vincent G; Schinkel-Ivy, Alison; Brooks, Dina; Inness, Elizabeth L; Mochizuki, George
Abstract : Objectives: No intervention has been shown to prevent falls poststroke. We aimed to determine if perturbation-based balance training (PBT) can reduce falls in daily life among individuals with chronic stroke. Design: Assessor-blinded randomised controlled trial. Setting: Two academic hospitals in an urban area. Interventions: Participants were allocated using stratified blocked randomisation to either 'traditional' balance training (control) or PBT. PBT focused on improving responses to instability, whereas traditional balance training focused on maintaining stability during functional tasks. Training sessions were 1 hour twice/week for 6 weeks. Participants were also invited to complete 2 'booster' training sessions during the follow-up. Participants: Eighty-eight participants with chronic stroke (>6 months poststroke) were recruited and randomly allocated one of the two interventions. Five participants withdrew; 42 (control) and 41 (PBT group) were included in the analysis. Primary and secondary outcome measures: The primary outcome was rate of falls in the 12 months post-training. Negative binomial regression was used to compare fall rates between groups. Secondary outcomes were measures of balance, mobility, balance confidence, physical activity and social integration. Results: PBT participants reported 53 falls (1.45 falls/person-year) and control participants reported 64 falls (1.72 falls/person-year; rate ratio: 0.85(0.42 to 1.69); p=0.63). Per-protocol analysis included 32 PBT and 34 control participants who completed at least 10/12 initial training sessions and 1 booster session. Within this subset, PBT participants reported 32 falls (1.07 falls/person-year) and control participants reported 57 falls (1.75 falls/person-year; rate ratio: 0.62(0.29 to 1.30); p=0.20). PBT participants had greater improvement in reactive balance control than the control group, and these improvements were sustained 12 months post-training. There were no intervention-related serious adverse effects. Conclusions: The results are inconclusive. PBT may help to prevent falls in daily life poststroke, but ongoing training may be required to maintain the benefits. Trial registration number: ISRCTN05434601 ; Results.